Le corps au cœur de la sémiose dans l'action didactique conjointe. Illustration en éducation musicale à l'école primaire au sein du dispositif DEMOS - Maël Le Paven; Marianne Nillès (Nantes Université, 2021)
This study focuses on semiosis (production and decoding of signs) in teacher / students and students / students joint action in fourth grade during musical education courses followed within the DEMOS device (Dispositif d'Education Musicale et Orchestrale à vocation Sociale), aimed at opening access to musical learning and practice in a symphonic orchestra to students from neighbourhoods under the city's policy or from rural areas with few cultural institutions. This work is based on a case study of trumpet lessons conducted by a teacher from a conservatory with a regional outreach. It is part of the Joint Action Theory in Didactics. Based on filmed excerpts from a teaching sequence and interviews with the teacher, we show how the ingenuity she develops in order to teach instrumental practice to a group of five students without going through prior written work, leads this group to co-construct a system of signs that allows it to appropriate the knowledge necessary for the production of a common artwork. Based on the concept of semiosis as defined by the Collective Didactique Pour Enseigner (2019), we analyse how these signs, which place the body at the heart of teaching-learning strategies, promote the individual and collective adjustments necessary for the development of skills that, going beyond the mere "musical" learnings, are in line with the socialization issues of the DEMOS project.